Efecto del programa educativo aprendizaje basado en problemas en el logro de la competencia construye interpretaciones históricas del área de ciencias sociales en los estudiantes de cuarto grado nivel secundaria en la Institución Educativa Teniente Manuel Clavero Muga Distrito De Punchana 2022 - Izquierdo Gonzales, Victor Antonio (2024)
The purpose of the research was to evaluate the effect of the Problem-Based Learning educational program on the development of the competence of constructing historical interpretations in the area of social sciences for fourth-grade secondary school students of the I.E. Lieutenant Manuel Clavero Muga, in the Punchana district, during the year 2022. The study used an evaluative approach, using a quasi-experimental design with pre- and post-tests. The study consisted of two groups: an experimental group that included 30 high school students and a control group consisting of 30 high school students. The participants were deliberately chosen to receive the program. The study used the Mann-Whitney U test to analyze the difference in means. The results indicate a notable disparity in the academic achievement of students who were exposed to the problem-based learning (PBL) program in comparison to those in the control group, particularly in relation to historical interpretations. The research found that the implementation of the problem-based learning program greatly enhances the comprehension and formation of historical interpretations in fourth grade students at the secondary level. The experimental group had a much greater percentage of early completion, achieving 74.2%, in contrast to the control group's rate of 33.3%.